PARADIGMA BARU BIMBINGAN PRA NIKAH: INTEGRASI MAQASID SYARIAH DAN FIKIH SYAFI’I UNTUK MEMBANGUN KETAHANAN KELUARGA - Wildan Miftahussurur; Saini; Moh. Jeweherul Kalamiah (Syariah: Jurnal Hukum Keluarga Islam, 2025)
This study aims to examine the implementation of pre-marital guidance at the Office of Religious Affairs (KUA) Tamanan, Bondowoso, through the perspective of maqasid al-shariah and Shafi’i jurisprudence. The research is motivated by the high divorce rate resulting from the lack of preparedness among couples to build a harmonious household. Using a qualitative approach and case study design, data were collected through in-depth interviews with the Head of KUA, religious counselors, and participants, as well as direct observation of program activities. Thematic analysis was employed by linking empirical findings with the principles of maqasid al-shariah and classical jurisprudence. The results indicate that pre-marital guidance at KUA Tamanan is not merely an administrative requirement but serves as a strategic instrument for internalizing five fundamental objectives of maqasid: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). The program integrates positive law, maqasid values, and Shafi’i jurisprudence through references such as Fath al-Qarib, combined with practical skills in communication, financial management, and reproductive health. This integration strengthens both religious legitimacy and practical relevance. The study recommends extending program duration, developing digital modules, and providing post-marital counseling to enhance value internalization. The findings contribute theoretically to Islamic family law discourse and practically to national pre-marital guidance policies.